1969
DOI: 10.1128/aem.18.6.965-971.1969
|View full text |Cite
|
Sign up to set email alerts
|

Algal Flocculation with Synthetic Organic Polyelectrolytes

Abstract: The feasibility of removing algae from water and wastewater by chemical flocculation techniques was investigated. Mixed cultures of algae were obtained from both continuousand batch-fed laboratory reactors. Representative cationic, anionic, and nonionic synthetic organic polyelectrolytes were used as flocculants. Under the experimental conditions, chemically induced algal flocculation occurred with the addition of cationic polyelectrolyte, but not with anionic or nonionic polymers, although attachment of all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(36 citation statements)
references
References 1 publication
1
35
0
Order By: Relevance
“…Knuckey et al [25] reported that the non-ionic polymer Magnafloc LT25 settled a wide range of microalgae species effectively using a rate of 0.5 mg/L in a pH adjusted media to 10-10.6. Tenney et al [172] noted the most effective flocculation resulted when using cationic polyelectrolytes at low pH levels. Ras et al [47] noted that the Chlorella species flocculated when the pH was increased to 11-12.…”
Section: Organic Flocculationmentioning
confidence: 99%
See 2 more Smart Citations
“…Knuckey et al [25] reported that the non-ionic polymer Magnafloc LT25 settled a wide range of microalgae species effectively using a rate of 0.5 mg/L in a pH adjusted media to 10-10.6. Tenney et al [172] noted the most effective flocculation resulted when using cationic polyelectrolytes at low pH levels. Ras et al [47] noted that the Chlorella species flocculated when the pH was increased to 11-12.…”
Section: Organic Flocculationmentioning
confidence: 99%
“…The polyelectrolyte charge plays an important role in the flocculation process of microalgae. Anionic polyelectrolytes are not effective flocculent agents on their own due to the negatively charged microalgae cell surface because like charges repel one another and/or the length of the polymer is not sufficient enough to bridge the particles together [142,172]. It is for this reason that cationic polyelectrolytes are found to be much more effective in the flocculation of microalgae.…”
Section: Charge On Polymermentioning
confidence: 99%
See 1 more Smart Citation
“…Another promising approach is to select for algae with the best settling properties by recycling settled algal cells to the treatment ponds the microalgae were initially harvested from [16,23], and [24]. Salim et al [24] observed that three microalgae (Scenedesmus obliquus, Tetraselmis suecica, and Ankistrodesms falcatus) appeared to improve recovery efficiency (settling) of two difficult-to-settle cultures of microalgae (C. vulgaris and Neochloris oleoabundans).…”
Section: Introductionmentioning
confidence: 99%
“…polyacrylamide, alginate, starches) to aggregate algae, and spreading of minerals (e.g. yellow loess, montmorillonite, kaolinite) for clay-based flocculation (Tenney et al, 1969;Sridhar et al, 1988;Sengco and Anderson, 2004). However, these methods are limited by low efficiencies and also have the capacity to disrupt marine ecosystems.…”
Section: Introductionmentioning
confidence: 99%